Third Five Year Plan Madras Draft Outline - Planning Commission (Planning Commission)
Summary Statement of Plan Outlay, Proposed List of Schemes Carried over from the Second Plan list of New Schemes Proposed for Inclusion list of agricultural research schemes contemplated for execution in third Five Year Plan period. Serial number and name of the scheme phasing of Proposed outlay. Statement for principal projects Proposed In Draft State Plan. Principal projects proposed in draft state plan
Madras Finance (P and D) Department